FENOMENAL YOESBAR DJAELANI SEBAGAI TOKOH MUSIK INDONESIA (SEBUAH BIOGRAFI) - Ayu Rizal; Awerman Awerman; Wilma Sriwulan (Institut Seni Indonesia Padang Panjang, 2017)
ABSTRACT The title of this writing is “The Phenomenal Yoesbar Djaelani as The Figure of Indonesian Music (A Biography).” Its discussion emphasizes on the study of assumptions about the figure phenomenon, Yoesbar Djaelani as an Indonesian composer. This reality is based on the achievement of Yoesbar Djaelani’s creativity as the participant of Pekan Komponis Muda (in English is translated into Young Composer Week) in 1976 and in 1977 organized Jakarta Art Council in Ismail Marzuki Park, Jakarta.Those assumptions have been documented in the various books of Indonesian music education such as the books of Music History, Music Appreciation, and Music Encyclopedia. Therefore, those assumptions above have been realized into facts since those books firstly published in the 1990s and that means until 2015, it has been 25 years.The above outlook becomes a phenomenon in musicology point of view because, in Indonesia, there are many definitions and translations toward composer. Nowadays, the composer of traditional music, the composer of dance accompaniment music, songwriter, arranger, and much more are also called as a composer. After going through contextually long and deep investigation about the composer and being supported by historical and musicological reviews, it can be concluded that Yoesbar Djaelani’s position has fulfilled the requirement as one of the Indonesian music figures. Keywords: Phenomenon, Composer, Music Figure, Biography.